2022
DOI: 10.3390/ijerph19074369
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Ex Vivo Approach Based on Proteomics and Biomarkers to Evaluate the Effects of Chrysene, MEHP, and PBDE-47 on Loggerhead Sea Turtles (Caretta caretta)

Abstract: The principal aim of the present study was to develop and apply novel ex vivo tests as an alternative to cell cultures able to evaluate the possible effects of emerging and legacy contaminants in Caretta caretta. To this end, we performed ex vivo experiments on non-invasively collected whole-blood and skin-biopsy slices treated with chrysene, MEHP, or PBDE-47. Blood samples were tested by oxidative stress (TAS), immune system (respiratory burst, lysozyme, and complement system), and genotoxicity (ENA assay) bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 153 publications
(188 reference statements)
0
7
0
Order By: Relevance
“…The dramatic increase in FP prevalence since the 1980s is attributed to a virus, and an unknown environmental factor thought to be anthropogenic in nature [68][69][70]. Results from genomic [71], proteomic [72][73][74] and transcriptomic studies [70,75,76] have consistently identified immune genes as dysregulated between healthy and diseased turtles or by levels of exposure to marine contaminants [73]. Additionally, sea turtles are possible reservoirs for zoonotic viruses, as C. mydas, along with snakes and pangolins, have been suggested as potential intermediate hosts of SARS-CoV-2 [77].…”
Section: Chelydra Serpentinamentioning
confidence: 99%
See 4 more Smart Citations
“…The dramatic increase in FP prevalence since the 1980s is attributed to a virus, and an unknown environmental factor thought to be anthropogenic in nature [68][69][70]. Results from genomic [71], proteomic [72][73][74] and transcriptomic studies [70,75,76] have consistently identified immune genes as dysregulated between healthy and diseased turtles or by levels of exposure to marine contaminants [73]. Additionally, sea turtles are possible reservoirs for zoonotic viruses, as C. mydas, along with snakes and pangolins, have been suggested as potential intermediate hosts of SARS-CoV-2 [77].…”
Section: Chelydra Serpentinamentioning
confidence: 99%
“…Studies of sea turtle immune function have been focused on the protection and conservation of turtle wildlife from threats such as FP, parasites, or environmental contaminants [42,[49][50][51][52][53][54][55][56]73,75,76,[88][89][90][91][92]. Functional studies of the turtle immune system have been carried out on red-eared slider turtles Trachemys scripta (Thunberg, 1792)) [19][20][21][22][23], Caspian turtle or striped-neck terrapin (Mauremys capsica (Gmelin, 1774)) [27][28][29][30][31] and Chinese softshelled turtle (Pelodiscus sinensis (Wiegmann, 1853)) [14,87,87,93].…”
Section: Chelydra Serpentinamentioning
confidence: 99%
See 3 more Smart Citations